2022
DOI: 10.1136/bmjopen-2022-062463
|View full text |Cite
|
Sign up to set email alerts
|

Vocal biomarker predicts fatigue in people with COVID-19: results from the prospective Predi-COVID cohort study

Abstract: ObjectiveTo develop a vocal biomarker for fatigue monitoring in people with COVID-19.DesignProspective cohort study.SettingPredi-COVID data between May 2020 and May 2021.ParticipantsA total of 1772 voice recordings were used to train an AI-based algorithm to predict fatigue, stratified by gender and smartphone’s operating system (Android/iOS). The recordings were collected from 296 participants tracked for 2 weeks following SARS-CoV-2 infection.Primary and secondary outcome measuresFour machine learning algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…We also observed that only the AIS obtained a good performance for age (AIS Age DR=0.77), and, except for PHQ-9 and GAD-7, all DRs were satisfactory or high for sex. Participants are grouped into age categories to allow analysis: [18,30), [30,45), [45,65), >65…”
Section: Clinical Threshold Detection (Classification)mentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that only the AIS obtained a good performance for age (AIS Age DR=0.77), and, except for PHQ-9 and GAD-7, all DRs were satisfactory or high for sex. Participants are grouped into age categories to allow analysis: [18,30), [30,45), [45,65), >65…”
Section: Clinical Threshold Detection (Classification)mentioning
confidence: 99%
“…The study of speech biomarkers in mental health holds great potential, offering a non-invasive and easily accessible avenue to capture significant motor, cognitive and behavioral changes due to mental health disorders such as depression and anxiety [10][11][12][13]. Clinical evidence and research studies have increasingly linked specific automated extracted speech features, such as prosody, articulation, and fluency, with various mental health conditions, including depression [10,14], anxiety [15], suicide-risk assessment [16], fatigue [17,18], or sleep deprivation [19]. The complexity of human speech extends beyond the intricate motor coordination involved.…”
Section: Introductionmentioning
confidence: 99%
“…To date, almost 6000 voice recordings from more than >500 patients with COVID-19 have already been collected in the Predi-COVID study [2]. These voice recordings have been analyzed, and promising vocal biomarker candidates for fatigue, loss of taste and smell, and symptomatic status in people with a COVID-19 infection have already been identified [20][21][22].…”
Section: Vocal Biomarkers Of Covid-19 Symptomsmentioning
confidence: 99%
“…Additionally, the COVID-19 pandemic generated increased interest in developing technology to perform remote, minimally invasive respiratory disease diagnostics, and voicederived biomarkers have come to the forefront of this effort. [3][4][5][6][7] Many groups have also found grounds for the analysis of voice for the detection and progression of neurological disorders, such as Parkinson's, Alzheimer's, Huntington's, and dementia. [8][9][10][11][12][13][14][15][16] Additional areas of investigation include pediatric and adult voice disorders, and mental health disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The vocal biomarkers market was worth USD 1901.1 million in 2021 and is expected to reach USD 5131.8 million in 2028 2 . Additionally, the COVID‐19 pandemic generated increased interest in developing technology to perform remote, minimally invasive respiratory disease diagnostics, and voice‐derived biomarkers have come to the forefront of this effort 3–7 . Many groups have also found grounds for the analysis of voice for the detection and progression of neurological disorders, such as Parkinson's, Alzheimer's, Huntington's, and dementia 8–16 .…”
Section: Introductionmentioning
confidence: 99%